Emerging Microfluidic Approaches for Platelet Mechanobiology and Interplay With Circulatory Systems - Zhang, Yingqi; Ramasundara, Savindi De Zoysa; Preketes-tardiani, Renee Ellen; Cheng, Vivian; Lu, Hongxu; Ju, Lining Arnold (Frontiers in Cardiovascular Medicine, 2021)
Platelet plays an important role in the pathogenesis of thrombosis governed by a range of biochemical and biomechanical factors particularly hemodynamic forces. It has been identified that the platelet is capable of sensing and responding to the flow disturbances caused by pathologically high shear and vessel geometries. The emerging lab-on-a-chip devices have facilitated platelet mechanobiology study by incorporating diverse structural and functional designs that mimic anatomical and physiological microenvironment in vitro. The crosstalk between platelets and the circulatory system, including von Willebrand factor and the vessel walls can be recapitulated in an endothelial cell-lined microfluidic device. Here, we highlight the advances of the microfluidic systems, that have been used to unravel how platelet mechanobiology and platelet-circulatory system interplay affect thrombotic processes. We then discussed the requirements of microfluidic standardization towards to industrialization, which stimulate the rising of commercialized microfluidic platforms for standardized and translational platelet and thrombosis research.